Cervical spine mechanical deficits in patients with shoulder impingement syndrome: A case-control study - Ramadan El-desoqi, Fatma Eldesoqi; Abdal Majeed, Salwa Fadl; Azzam, Ahmad Hamdy; Mohammed Sarhan, Mohammed Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this case-control study was to investigate whether cervical mechanical deficits differ between patients with shoulder impingement syndrome (SIS) and control subjects. A total of 40 non-athletic males and females participated in this study. They were divided into two groups: group A, including 20 patients with SIS with a mean age of 36 years, and group B, including 20 control subjects with a mean age of 34 years. Each participant was assessed for pain and disability using shoulder pain and disability index (SPADI), active joint angular reproduction (AJAR) at 30o cervical flexion and extension using inclinometer, and craniovertebral angle (CVA) using photography. The results of the study showed that there was a statistically significant positive correlation between AJAR error at 30o cervical flexion and both shoulder pain and disability (r > 3, p = <0.05), and also a statically significant difference between groups at AJAR error in extension (t = 3.8, p = 0.000). In conclusion, cervical proprioception deficits showed a significant correlation with shoulder pain and disability in patients with SIS.